Nuclide composition dynamics in a subcritical reactor driven by a proton beam - Demchenko, P.O.; Gussev, Ye.V.; Nikolaichuk, L.I. (Вопросы атомной науки и техники, 2004)
The numerical simulation results of nuclide composition time dynamics in a subcritical reactor blanket are given.
A cylindrical subcritical reactor is driven by a high-energy proton beam injected along the radius into the reactor
blanket. The initial blanket substance was the fertile uranium with different energetic plutonium concentration. Надано результати чисельного моделювання зміни з часом нуклідного складу бланкета підкритичного
реактора з радіальною інжекцією протонного пучка. Матеріалом бланкету є збіднений уран з різною концентрацією енергетичного плутонію. Приведены результаты численного моделирования изменения во времени нуклидного состава бланкета
подкритического реактора при радиальной инжекции протонного пучка. Веществом бланкета является обеднённый уран с различной концентрацией энергетического плутония.